Unique nanostructural features in Fe, Mn-doped YBCO thin films. (21st October 2016) - Meledin, A; Turner, S; Cayado, P; Mundet, B; Solano, E; Ricart, S; Ros, J; Puig, T; Obradors, X; Van Tendeloo, G
Abstract: An attempt to grow a thin epitaxial composite film of YBa2 Cu3 O7− δ (YBCO) with spinel MnFe2 O4 (MFO) nanoparticles on a LAO substrate using the CSD approach resulted in a decomposition of the spinel and various doping modes of YBCO with the Fe and Mn cations. These nanostructural effects lead to a lowering of T c and a slight J c increase in field. Using a combination of advanced transmission electron microscopy (TEM) techniques such as atomic resolution high-angle annular dark field scanning TEM, energy dispersive x-ray spectroscopy and electron energy-loss spectroscopy we have been able to decipher and characterize the effects of the Fe and Mn doping on the film architecture. The YBaCuFeO5 anion-deficient double perovskite phase was detected in the form of 3D inclusions as well as epitaxially grown lamellas within the YBCO matrix. These nano-inclusions play a positive role as pinning centers responsible for the J c / J sf ( H ) dependency smoothening at high magnetic fields in the YBCO-MFO films with respect to the pristine YBCO films.